AN ANALYSIS OF TEACHER’S SOCIAL MEDIA AND ITS RELATION TO POLITENESS THEORY - Candra Dewi, Made Raninta; Padmadewi, Ni Nyoman; Artini, Luh Putu (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
The involvement of social media in people’s life marks the beginning of the Industrial Revolution 5.0. The abundance of post in social media can creat a public image of a certain professional. It also includes the creation of public image of a teacher. Teachers as a part of society also upload pictures and videos, but apparently they consider their job as to create a certain perception about themselves in front of the society. This study aims to examine the language used on teachers’ social media accounts in relation to face saving theory and politeness strategy. The data was gatherered from individuals who commented on these social media posts. The study involves two teachers who are actively engaged on social media platform. It employs a basic qualitative research approach, with data collected through observation. Thematic analysis was applied to interpret the observed data. The result reveal that the teachers maintain a positive self image by showcasing their achievements, professional experiences, and personal lifestyles online. Meanwhile, their followers tend to use positive politeness strategies, such as expressing appreciation and highlighting similarities, to acknowledge and support the teachers’ positive self presentation. The finding of this study enrich the theory of the politeness strategy used by a teacher to create their public image. The perception of students toward teacher’s public image can affect how the learning process is achieved later on in practical way.